How Much Do They Make? New Evidence on the Early Career Earnings of Canadian Trade Certificate (Journal of Organizational Psychology, 2021)
This paper provides new evidence on the early career earnings of Canadians who obtain a trade certificate. The analysis uses comprehensive national level administrative data on individuals who received a trade certificate between 2008 and 2016 linked to their tax information at Statistics Canada in order to link earnings to their individual characteristics and details related to their certification. In this paper we track their yearly employment earnings from their first full year following certification onward, to a maximum of 9 years. Overall, journeypersons in nationally accredited Red Seal trades earn more than those in non-Red Seal trades, those in Mechanical and Electrical trades earn the most, and journeywomen earn only 47% of what journeymen do overall, largely driven by their being concentrated in a relatively narrow set of low-paying trades.
Keywords: organizational psychology; trades; apprenticeship; earnings; labour market; skills